Eckert animal physiology: Mechanisms and adaptations - Randall, David; Randall, David; Burggren, Warren; French, Kathleen (New York, W H Freeman Company, 2002)
This classic animal physiology text focuses on comparative examples that illustrate the general principles of physiology at all levels of organization$1 (Bfrom molecular mechanisms to regulated physiological systems to whole organisms in their environment.s
Glossary G1-G24p.; Bibliographical References R1-R8p.; Appendix A1-A4p.; Index I1-I20p.
Keywords: Physiology; Zoology